Peryfraza progresywna i strategie tekstowe - Jakielaszek, Jarosław (Vox Patrum, 2004)
One of the most striking features of Lucifer’s style is his frequent usage of a periphrastic structure. The paper proposes that there is a clear semantic distinction between this construction and synthetic verbal forms. Stylistic and interpretive consequences of Lucifer’s usage follow from a comparison with other authors and transtextual gestures which determine a proper contextualization of such structures.